2017
DOI: 10.1017/s0025315416001909
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in oxidative stress indicators in liver of totoaba (Totoaba macdonaldi) Perciformes: Sciaenidae

Abstract: Several characteristics of Totoaba macdonaldi Perciformes: Sciaenidae, including migratory movements along temperature gradients make it vulnerable to oxidative stress. Oxidative stress can also be associated with reproduction. The objectives of the present study were to examine oxidative stress indicators in liver of totoaba throughout the seasons (spring, autumn and winter), and the associated fluctuations in superficial sea temperature (SST, °C), as well as to evaluate possible variations between sexes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…PUFAs are highly susceptible to ROS attack, which results in lipid peroxidation (34). The high production of ROS as a result of a stress condition during migration can cause increased lipid peroxidation in the liver (35). In the present study, MDA level also increased in the white muscle of fishes sampled from the stream.…”
Section: Biochemical Analysessupporting
confidence: 63%
“…PUFAs are highly susceptible to ROS attack, which results in lipid peroxidation (34). The high production of ROS as a result of a stress condition during migration can cause increased lipid peroxidation in the liver (35). In the present study, MDA level also increased in the white muscle of fishes sampled from the stream.…”
Section: Biochemical Analysessupporting
confidence: 63%
“…Extreme environmental conditions occur in the northern Gulf of California, especially the delta area. Variations in the oxidative stress indicators in response to changes in biotic and abiotic factors have been previously reported in several fish species ( Aras et al, 2009 ; Pavlović et al, 2010 ; Oliva et al, 2012 ), including T. macdonaldi ( Hernández-Aguilar et al, 2017 ). Results from this study suggest that totoaba faces spatial–temporal variation in muscle oxidative stress indicators that may be associated to a complex interaction between environmental and biological factors, including food availability and temperature.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study, liver superoxide dismutase (SOD) activity was found to be related to totoaba’s maturity stage ( Hernández-Aguilar et al, 2018 ); thus, it was used in this study to further discriminate between environmental and physiologic effects on trace element content in totoaba. This third GLM explains 55% of the variance and suggests that in liver, SOD activity is inversely related to Cd concentration in winter and spring ( p < 0.05) but not in autumn ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The GLMs constructed in this study suggest that liver Cd concentration varies inversely with liver Zn concentration, that liver Cd content affects muscle Cd concentrations, and that in the liver, SOD activity is inversely related to Cd concentration and length of the organisms. The totoaba collected in autumn have the highest liver Cd concentrations, and the highest SOD activity ( Hernández-Aguilar et al, 2018 ). In autumn, immature and undifferentiated totoabas feed on sardines and crustaceans ( Cisneros-Mata, Montemayor-Lopez & Roman-Rodriguez, 1995 ).…”
Section: Discussionmentioning
confidence: 99%